1994
DOI: 10.1111/j.1749-7345.1994.tb00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Microbial Environment of Rotifer Brahionis plicatilis and Avtemia Production Systems

Abstract: Samplings were organized in three marine fish hatcheries. Samples were taken at different steps during the production of algae, rotifers and Artemia. There were 233 dominant colony types isolated for further characterization. The isolates were compared to each other and to reference strains of Phorobacrerium, Yibrio and Alreromonas, using cellular fatty acid fingerprints. Fatty acid profiles of the isolates were grouped using principal component analysis. The isolates fell into at least ten major groups, of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 12 publications
0
27
0
3
Order By: Relevance
“…Several cultivation-dependent and independent studies have showed that vibrios appear at particularly high densities in and/or on marine organisms, e.g., corals (331), fish (6,146,179,325), molluscs (345), seagrass, sponges, shrimp (133,(404)(405)(406) and zooplankton (163,194,365,408,409).…”
Section: According To Bergey's Manual Of Determinative Bacteriologymentioning
confidence: 99%
“…Several cultivation-dependent and independent studies have showed that vibrios appear at particularly high densities in and/or on marine organisms, e.g., corals (331), fish (6,146,179,325), molluscs (345), seagrass, sponges, shrimp (133,(404)(405)(406) and zooplankton (163,194,365,408,409).…”
Section: According To Bergey's Manual Of Determinative Bacteriologymentioning
confidence: 99%
“…Bacterial infections, especially those generated by the genus Vibrio, create serious mortality problems in the culture of larval stages. It is not possible to develop these cultures in sterile media, but the potential sources of contamination can be controlled by treating the water by filtration or UV irradiation (Liltved et al, 1995) and, in the larviculture of fish and crustaceans, by improving the sanitary quality of the Artemia nauplii used as food because they can become an important vector for the transmission of Vibrio and other pathogenic bacteria (Verdonck et al, 1994;Liz谩rraga-Partida et al, 1997). Due to the lack of information regarding the bacterial flora associated with the Mexican populations of Artemia, nauplii obtained from cysts from several sites in Mexico were analyzed in this study.…”
Section: Materiales Y M茅todosmentioning
confidence: 99%
“…Las infecciones bacterianas, especialmente las generadas por el g茅nero Vibrio, causan grandes problemas de mortalidad en la etapa de larvicultura. No es posible desarrollar estos cultivos en medios est茅riles, pero se pueden controlar las fuentes potenciales de contaminaci贸n tratando el agua por filtraci贸n y por luz ultravioleta (Liltved et al, 1995) y, en la larvicultura de peces y crust谩ceos, mejorando la calidad sanitaria de los nauplios de Artemia usados como alimento debido a que pueden constituirse en un vector importante para la transmisi贸n de Vibrio y otras bacterias pat贸genas (Verdonck et al, 1994;Liz谩rraga-Partida et al, 1997).…”
Section: Introductionunclassified
“…Many studies were carried out on the mass culture of rotifers with different microalgal diets and at different temperatures and salinity conditions (Fielder et al, 2000;Hotos, 2002Hotos, , 2003Savas and Guclu, 2006;Kostopoulou and Vadstein, 2007;Jabeur et al, 2013;Abou-Shanab et al, 2016) in the rotifer tanks. Several researchers reported variations in rotifer density due to Vibrio infections which is a major constraint for high density production of rotifers (Skjermo and Vadstein, 1993;Verdonck et al, 1994Verdonck et al, , 1997Gomez-Gil et al, 2000;Rombaut et al, 2001;Prol-Garcia et al, 2010, Jayasree et al, 2016. Use of antibiotics in culture systems will lead to the development of antibiotic resistant strains of pathogenic bacteria and will also hinder the growth of cultured organisms.…”
mentioning
confidence: 99%